PROSES KREATIF PENCIPTAAN TARI JEPIN TERUNE OLEH SAUNIHAR DI SANGGAR ALE-ALE KABUPATEN KETAPANG KALIMANTAN BARAT - Putri, Fakhrani Anugrah; Ismunandar, Ismunandar; Satrianingsih, Aline Rizky Oktaviari (Universitas Tanjungpura, 2023)
This research was motivated to find out the creative process of dance creation carried out by Saunihar as well as the choreographic form of Jepin Terune Dance. This form of research uses qualitative and descriptive research methods with a choreographic approach. Data collection for this study used interviews with speakers, observation,s and documentation studies. The technique tests the validity of the data by extending observations and triangulating sources. The focus of this research is the form of choreography and the creative process of creation by Saunihar on the Jepin Terune Dance. The results of the study can be concluded that the Jepin Terune Dance was created by Saunihar in 2014 for a National Malay Cultural Arts Festival competition and won the first place award. The factors that influenced Saunihar when creating the Jepin Terune Dance came from internal (oneself) and external (family, work, and society). Through the exploration stage on the movement of martial arts flowers at 7-12 and community activities that use canoe and bicycle transportation. The improvisation carried out is based on the idea of ideas and movements from the Jepin Step Dance. Jepin Terune dance has a theme of natural beauty and is danced by an even number of male dancers accompanied by Malay musical instruments such as selodang, tambourine, beruas, vocal fibers.